Aflatoxin exposure and mortality in acutely ill children: results from the CHAIN network cohort - Tahmeed Ahmed; Molline Timbwa; Moses Ngari; Mohammod Jobayer Chisti; Kirkby D Tickell; Hama Diallo; Robert Bandsma; Judd L Walson; Syed Asad Ali; James Berkley; Ezekiel Mupere; Ali Faisal Saleem; et al. (BMJ Global Health, 2025)
Background Chronic exposure to aflatoxins is associated with liver cancer, impaired child growth, and compromised immune function. The Childhood Acute Illness and Nutrition (CHAIN) Network cohort was established to identify risk factors for mortality in acutely ill children admitted to nine hospitals in four African and two South Asian countries. We examined the role of aflatoxin exposure in inpatient and post-discharge mortality.Methods In a nested case-cohort from the CHAIN cohort, we compared aflatoxin exposure at admission and discharge with death or survival in hospital (n=755) or up to 180-days post-discharge (n=585) and with community participants (CP, n=222). Children were stratified into non-wasting, medium-wasting and severe-wasting groups based on mid-upper arm circumference. Serum samples were analysed for an aflatoxin exposure biomarker, the aflatoxin-albumin adduct (AF-alb) using ELISA.Findings Overall, 56% of hospitalised participants tested positive for AF-alb at admission. The AF-alb level was higher in deceased (geometric mean and 95% CI (GM and 95% CI) 5.9 (4.9 to 7.1)) than in survivors (4.2 (3.8 to 4.7)) and CP (3.7 (3.1 to 4.3)) pg/mg alb. AF-alb concentration was higher at admission (4.7, (4.2 to 5.1)) than at discharge (3.7, (3.3 to 4.1)) and in the CP group (3.7, (3.1 to 4.3)) pg/mg alb (p<0.01) and in African vs Asian children (7.4 (6.5 to 8.5) vs 1.9 (1.8 to 2.1)) (p<0.001). Adjusted logistical regression showed no significant association between AF-alb levels and mortality, but after separating the nutrition strata, AF-alb was significantly associated with mortality (highest vs lowest quartile group OR=4.84, p=0.014) in non-wasted children.Interpretation Moderate to severe malnutrition is a more important risk factor for mortality than aflatoxin in acutely ill children, but aflatoxin exposure may contribute to mortality in non-wasted children. Controlling aflatoxin exposure should be integrated into clinical and public health interventions to reduce mortality in areas with high levels of exposure.Funding Bill and Melinda Gates Foundation (OPP1131320 & INV-003225).